2013
DOI: 10.1007/s00259-013-2580-y
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of focal uptake in head and neck tumours: 18F-FDG PET/MR versus PET/CT

Abstract: PurposeOur objectives were to assess the quality of PET images and coregistered anatomic images obtained with PET/MR, to evaluate the detection of focal uptake and SUV, and to compare these findings with those of PET/CT in patients with head and neck tumours.MethodsThe study group comprised 32 consecutive patients with malignant head and neck tumours who underwent whole-body 18F-FDG PET/MR and PET/CT. PET images were reconstructed using the attenuation correction sequence for PET/MR and CT for PET/CT. Two expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 36 publications
2
94
0
Order By: Relevance
“…Despite the sometimes large differences between uptake times, most studies came to the conclusion that there was a high positive correlation for all SUV quantification metrics between both exams and that most of the differences were due to the variance in uptake time between both scans [44-48, 50, 51, 53, 54, 57, 59-61, 64]. In only two studies, some scans were performed on the PET/MR scanner first [52,58], and in two studies, all PET/MR scans were performed before PET/CT [49,56]. All other studies had a longer uptake time of 51-120 min (mean 81 min) for the PET/MR scans and showed a slight increase in SUV between both exams.…”
Section: Clinical Studies Comparing Suv Measurements Between Pet/ct Amentioning
confidence: 99%
“…Despite the sometimes large differences between uptake times, most studies came to the conclusion that there was a high positive correlation for all SUV quantification metrics between both exams and that most of the differences were due to the variance in uptake time between both scans [44-48, 50, 51, 53, 54, 57, 59-61, 64]. In only two studies, some scans were performed on the PET/MR scanner first [52,58], and in two studies, all PET/MR scans were performed before PET/CT [49,56]. All other studies had a longer uptake time of 51-120 min (mean 81 min) for the PET/MR scans and showed a slight increase in SUV between both exams.…”
Section: Clinical Studies Comparing Suv Measurements Between Pet/ct Amentioning
confidence: 99%
“…A study by Varoquaux et al [53] compared PET/MR and PET/CT for the detection and quantification of focal uptake in H&N tumors. They found no significant difference in qualitative results regarding image quality, fusion quality, lesion conspicuity, and anatomic location of focal uptake.…”
Section: Pet/mrimentioning
confidence: 99%
“…Careful interpretation is needed for direct comparison of quantitative PET/MR and PET/CT results [86,87].…”
Section: Consideration For Study Protocolmentioning
confidence: 99%